Chronic Obstructive Pulmonary Disease and Non-Small Cell Lung Cancer an association - Zarogoulidis, Paul; Oikonomidou, Rena; Petridis, Dimitris; Huang, Haidong; Bai, Chong; Eleni-Isidora, Perdokouri; Vagionas, Anastasios; Hohenforst-Schmidt, Wolfgang; Kosmidis, Christoforos; Sapalidis, Konstantinos; Oikonomou, Panagoula; Nikolaou, Christina; et al. (Journal of Cancer, 2024)
Objectives: Lung cancer is known to be associated with chronic obstructive pulmonary disease. Moreover; nutritional status is associated with chronic obstructive disease treatment and lung cancer. Our aim was to evaluate the interaction of the COPD status and treatment of non-small cell lung cancer. Methods: Eighty-two patients were enrolled in our multicenter study. Chronic obstructive disease stage, spirometry and treatment was recorded along with the treatment and Body Mass Index (BMI), Mediterranian Diet Score, Pack Years, Basic Metabolsim (RMR) (kcal/day), VO2 (ml/min), Ve (lt/min) and Physical Activity. The statistical analysis was performed using the JMP 14.3 (SAS Inc 2018) software. Results: The drug pairs showed a steady and unchanged by time health condition for 48 patients. Overall, 31 patients were recorded with worse COPD health conditions. The one-way ANOVA clearly indicated that chemotherapy induced the best FEV1-difference conditions with a positive effect of 8.56 mean FEV volume, the combined treatment simply did not have an effect (-0.9), while immunotherapy and patients receiving radiation decreased their FEV1 volume down to -4.23 and -5.15 mean values. Conclusions: Patients receiving chemotherapy alone had their chronic obstructive disease improved with less drugs and exacerbations, while patients receiving immunotherapy had their chronic obstructive disease stable, while all other treatment combinations worsened the patients chronic obstructive disease. Nutritional status did not affect the chronic obstructive disease of these patients in any way.
CRIS-Team Scopus Importer:2024-05-24
Keywords: COPD; DLCO; NSCLC; Nutrition; spirometry